ERENDIDA NUEVA VARIEDAD DE PAPA RESISTENTE AL TIZON TARDIO - NIEDERHAUSER, JOHN S (My University, 1958)
no
CAMPO
Keywords: ERENDIDA, NUEVA, VARIEDAD, PAPA, RESISTENTE, TIZON, TARDIO; CIENCIAS AGRARIAS; AGRONOMIA; PRODUCCION DE CULTIVOS